Evaluation of ProximateandOrganoleptic Aspects of Silver Rasbora Fish (Rasbora lateristriata) Bekasam Based onDifferent Fermentation Duration and Salt Concentration - Rahmawati Rahmawati; Astrid Damayanti; Sri Djajati; Anugerah Dany Priyanto (Agroindustrial Technology Journal, 2021)
Silver rasbora fish (Rasbora lateristriata) is mainly consumed by Indonesian people and can be processed and preserved to be a traditional fish product called bekasam. Fermentation process of bekasam is influenced by several factors, including duration of fermentation and salt concentration. The objective of this research was to examine the influence of duration of fermentation and salt concentration on proximate composition and organoleptic aspects on silver rasbora fish bekasam. The experimentaldesign used in this research was a completely randomized design (CDR) with two factors, namely factor I (duration of fermentation: 4 days, 5 days, and 6 days) and factor II (salt concentration: 15%, 17,5%, and 20%). The results revealed that moisture and ash content of silver rasbora fish were in the range of 58,985-62,651% and 16,374 –19,872%. Organoleptic studies indicated that the highest score in flavour and taste were observed in bekasam fermented for 6 days with 15% salt concentration. The highest score in texture was found in bekasam fermented for 4 days with 20% salt concentration, whilst the lowest score was in bekasam fermented for 4 days with 15% salt concentration